Prestaciones del personal de enfermería para la atención del parto en mujeres indígenas. - Fray Peñafiel, Evelyn Tatiana (2025)
The research titled "Nursing Services for Childbirth Care in Indigenous Women" analyzes the performance of nursing staff in intercultural childbirth care, with a focus on promoting the participation of pregnant women and their families to ensure safe and culturally competent access to the institutional healthcare system. The general objective was to identify the nursing services that promote culturally appropriate access for indigenous women to institutional childbirth care. Methodologically, a mixed approach was used: surveys to collect quantitative data and qualitative interviews with nurses. The sample included pregnant indigenous women and nursing staff in an area of ethnic diversity. The results highlight the need for continuous training in cultural competence, as well as a demand for incorporating traditional midwifery practices and improving communication through bilingual interpreters. These elements foster greater trust and satisfaction in childbirth care. It is concluded that nursing services can be improved with an intercultural approach that respects cultural beliefs and practices, and that includes family participation in childbirth, which facilitates indigenous women's access to safe and culturally respectful healthcare services.